Establishing the John of God Movement in Australia: Healing, Hybridity and Cultural Appropriation - Rocha, Cristina (Ethnologies, 2011)
João de Deus (John of God) is a Brazilian faith healer who has been attracting a large number of followers outside his country. In the past decade, he has conducted international healing events in Germany, the US, and New Zealand, among others. As a consequence, John of God’s story has been told in documentaries on North American, British, Australian, and New Zealand television. Many of these documentaries have been uploaded by followers on You Tube. Such global exposure has been accompanied by intense flows of people, ideas, and commodities between Casa de Dom Inácio (John of God’s healing centre in Brazil) and these countries. In this paper, I track flows between Australia and Brazil. I argue that the position of Australia as a colonial-settler society, where the aboriginal population has suffered immense loss, entails a different understanding of John of God’s particular brand of Spiritism. For many followers, the arrival of the ‘entities’ (spirits John of God incorporates) is perceived as a way to heal the wounds of the land. Such understanding is not found among Spiritists and John of God followers in Brazil, although the country also has a history of dispossession and suffering among indigenous peoples.